Functional Endoscopic Sinus Surgery: Indications and Complications in the Ophthalmic Field - Al-Mujaini, Abdullah (OMJ, 2009)
Functional Endoscopic Sinus Surgery (FESS) is a highly sophisticated type of surgery, which has revolutionized the surgical management of chronic sinus diseases. In the ophthalmic field, FESS plays a crucial role in the management of a few conditions, but not without risks. Ophthalmic complications associated with FESS are well documented. They mainly occur due to the shared common anatomic areas between ophthalmology and otolaryngology. Ophthalmic complications can vary in severity from very trivial cases such as localized hematoma collection, which is not very problematic to very devastating cases, such as optic nerve damage, which can lead to complete blindness. In order to minimize such complications, safety measures need to be considered prio to the surgery, these include; precise knowledge of detailed anatomy, the operating surgeon’s ability to interpret precisely the para nasal sinus CT scan and experienced procedural surgical skills.